Impact of taxes on economic growth and SDG trajectory in Sri Lanka - Jayaweera, R.; Premaratna, S.P.; Priyanath, H.M.S.; Semasinghe, W.M.; Sumanadasa, M.; Hennayake, H.M.N.; Kodippili Arachchi, P.S. (Colombo Economic Journal, 2023)
Taxes play an extraordinary role in a country’s policymaking and economic growth. This study investigates the impact of direct and indirect taxes on economic growth in Sri Lanka. The impact of both direct and indirect taxes on economic growth in Sri Lanka was analyzed by employing the autoregressive distributed lag (ARDL) approach using time series data from 1990 to 2022. The results of the analysis suggest a positive and significant impact of indirect taxes on economic growth in the shortrun, but a negative impact in the long-run. Direct taxes have a negative and significant impact on growth in the short-run and the long-run. The results of the paper indicate that the tax structure in Sri Lanka does not help enhance the country’s economic growth, thereby delaying its progress toward achieving the Sustainable Development Goals (SDGs).
Keywords: ARDL; Direct taxes; Economic growth; Indirect taxes; Sri Lanka